Exploration of Health Literacy in Science Learning Curriculum in Indonesia - Insih Wilujeng; Muhammad Syamsussabri; Suyanta Suyanta; Endang Lasminawati (Postgraduate, University of Mataram, 2022)
This study aims to explore the integration of health literacy in science learning based on basic competencies and content of learning modules in science subjects in junior high schools in Indonesia. The modules analyzed are modules issued by the Indonesian government through the Indonesian Ministry of Education, Culture, Research and Technology issued in 2021. The method used in this study is document analysis. The main instrument used to analyze the module is the content analysis table. The data analysis technique used is the percentage technique. The results of the study indicate that the overall context of health literacy has been included in the science learning module with varying coverage based on the components of the health literacy context, and the student's grade level. The coverage of the identified health literacy context components, namely healthy life reached 20%, disease reached 37%, Hazard that Threaten Health reached 20%, Public Health 7%, and Applications of Science in the Field of Health reached 17%. In addition, based on the junior high school grade level, the context of health literacy is mostly contained in the 8th grade module, reaching 66% of the total basic competencies contained in the module, while the 7th grade reaches 54%, and the 9th grade reaches 40%.